(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Today the interest of educated people in economic theory is increasing more and more. This is explained by the global changes that are taking place all over the world. Practically everyone deals with economic issues and problems. Most interactions in society are directed and coordinated by certain rules of the game. In economic behavior, property rights form an extensive and important part of the rules. Economics explains social phenomena, the mechanism of interaction, and makes it possible to foresee the direction in the economic behavior of people. The purpose of this article is to study the economic education of students at the present time, to identify the problems of economic education at the institute, to suggest ways to solve them and to identify the importance of economic education for a modern student.